2020
DOI: 10.1055/s-0039-3402737
|View full text |Cite
|
Sign up to set email alerts
|

Vertigo Due to Vascular Mechanisms

Abstract: Isolated dizziness and vertigo due to vascular mechanisms are frequently misdiagnosed as peripheral vestibulopathy or vestibular migraine. For diagnosis of strokes presenting with an acute prolonged (≥ 24 hours) vestibular syndrome, findings on clinical examination, such as HINTS (negative head impulse tests, detection of direction-changing gaze-evoked nystagmus, and presence of skew deviation), are more sensitive than findings on neuroimaging. Since HINTS alone cannot securely detect anterior inferior cerebel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 102 publications
0
1
0
2
Order By: Relevance
“…Abnormalities in the vertebral arteries account for a large proportion of the causes of vascular dizziness. Many studies have showed that abnormalities in the carotid arteries are associated with symptoms of dizziness in patients (18,19). The vertebral artery-basilar artery ring supplies 1/5 of the blood flow to the brain, and stenosis of the VA may lead to hypoxia and ischemia in the brain, resulting in dizziness (20).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the vertebral arteries account for a large proportion of the causes of vascular dizziness. Many studies have showed that abnormalities in the carotid arteries are associated with symptoms of dizziness in patients (18,19). The vertebral artery-basilar artery ring supplies 1/5 of the blood flow to the brain, and stenosis of the VA may lead to hypoxia and ischemia in the brain, resulting in dizziness (20).…”
Section: Discussionmentioning
confidence: 99%
“…Большое значение современных стандартизированных диагностических клинических протоколов (например, HINTS, TriAGe+) для дифференциации симптома острого головокружения и быстрого выявления его потенциально опасных причин отметили в своем недавнем обзоре A. Zwergal и M. Dieterich. Они рекомендовали с осторожностью интерпретировать нейровизуализационные данные, полученные при МРТисследовании, так как высока вероятность недооценки небольших очагов поражения [5] и центральных вестибулярных нарушений (что обусловлено особенностями кровоснабжения данной артерией), протокол HINTS не столь информативен, в отличие от диагностики, например, инсульта в бассейне задней нижней мозжечковой артерии [30]. К аналогичному выводу пришли H. Lee и соавт., проведя проспективное наблюдение пациентов с инфарктом в бассейне передней нижней мозжечковой артерии, подтвержденным нейровизуализационным исследованием.…”
Section: нейровестибулярное обследование для дифференциального диагно...unclassified
“…В последнем случае (при инфаркте в бассейне лабиринтной артерии) развивается острый кохлеовестибулярный синдром [28]. Несмотря на то что инсульт в артериях ВБС часто проявляется головокружением в сочетании с очаговой неврологической симптоматикой, малые инфаркты с вовлечением нижней ножки мозжечка, узелка и вестибулярных ядер могут вызвать изолированное головокружение [29,30]. Первичная дифференциальная диагностика острого головокружения проводится в рамках острого вестибулярного синдрома, который, с использованием алгоритма NIHTS+ или его модификаций, далее подразделяется на центральный и периферический [31,32].…”
unclassified